2010
DOI: 10.1016/j.joca.2010.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Loading and knee alignment have significant influence on cartilage MRI T2 in porcine knee joints

Abstract: The response of T2 to change in static loading or alignment varied between the medial and lateral cartilages, and among the deep, intermediate, and superficial zones. These T2 changes were significantly related to the contact pressure measurements. Our results indicate that T2 mapping under loading allows non-invasive, biomechanical assessment of site-specific stress distribution in the cartilage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 35 publications
2
25
0
Order By: Relevance
“…There may also be little distinction in T 2 values within the spectrum of pre-radiographic to radiographic cartilage damage [34,90]. In addition to being affected by the angle at which cartilage is positioned with respect to the main magnetic field [55], T 2 values are sensitive to the type of radiofrequency coil [91], the choice of pulse sequence and sequence parameters [92], the joint position during imaging [93] and the type of equation used to fit data [94].…”
Section: T 2 Mappingmentioning
confidence: 99%
See 1 more Smart Citation
“…There may also be little distinction in T 2 values within the spectrum of pre-radiographic to radiographic cartilage damage [34,90]. In addition to being affected by the angle at which cartilage is positioned with respect to the main magnetic field [55], T 2 values are sensitive to the type of radiofrequency coil [91], the choice of pulse sequence and sequence parameters [92], the joint position during imaging [93] and the type of equation used to fit data [94].…”
Section: T 2 Mappingmentioning
confidence: 99%
“…Values for T 2 , T 1,Gd and T 1r , even in normal cartilage, differ in the literature and can be dependent on pulse sequence [92], the strength of the static magnetic field [32,119] and the radiofrequency coil [91]. A number of studies have shown that loading history [93,120 -122] and joint alignment [93,123] can also affect some of these qMRI measures. Additionally, despite correlations that show a difference in these qMRI measures between normal and damaged cartilage, there may be a lack of sensitivity in distinguishing the levels of clinical damage [37,90,124,125].…”
Section: Current Limitations Of Quantitative Magnetic Resonance Imagimentioning
confidence: 99%
“…After conducting the following imaging and mechanical experiments, macroscopic inspection of the joint surfaces did not reveal any signs of joint disease or cartilage degeneration in the specimens. The porcine knee joints were mounted in a custom-made nonmetallic compression device, which has been described in detail in the report of a previous loading experiment 18 . In brief, the femoral and tibial shafts were firmly fixed to the nonmobile base and the opposing side of the mobile plate respectively, and under static loading conditions at neutral or varus/valgus alignments, longitudinal compression force was transmitted to the knee joint through a sliding plate bounded by a viscoelastic foam material (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…1). When the foam material was compressed by 20 mm with a screw compression driver, the compression force was applied to the knee joint to achieve 300 N across the tibiofemoral cartilages 18 , which corresponded to approximately one-third of the body weight of the specimen.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation